Hydrothermal transformation of kaolinite in the system k₂osio₂al₂o₃h₂o (2010)
A kaoliniterich raw material was treated hydrothermally with 1.33 and 3.99M KOH solutions at 100 and 175 °C during different reaction times ranging from 24 to 528 h. The synthesis products were characterized by Xray diffraction, scanning electron microscopy, Fourier transform infrared spectroscopy, magic angle spinning nuclear magnetic resonance and thermogravimetric analysis in order to elucidate their physicochemical and mineralogical characteristics. The transformation of the starting material in KOH solutions can be explained by two different processes: (1) dissolution and (2) precipitation. A series of crystalline phases summarized by the reaction sequence kaolinite → chabazite → edingtonite → unidentified potassium aluminosilicate phase → kalsilite + leucite was identified in the system K₂OSiO₂Al₂O₃H₂O. The solid products show, on the other hand, remarkable textural and structural differences with the starting material.